Asphyxia from the eyes of the obstetrician - Alessandra Meloni; Vito Cofelice; Sara Francesca Deiana; Rossella Mereu; Giuliana Palmas; Vassilios Fanos; Gian Benedetto Melis (Hygeia Press di Corridori Marinella, 2014)
Nowadays it is well recognized that there are multiple potential pathways causing hypoxic-ischemic events that may lead to cerebral palsy in term infants. The signs and symptoms of neonatal encephalopathy may range from mild to severe, depending on nature and timing of brain injury. The incidence of cerebral palsy has not changed over the last 30 years and one of the obstetricians'challenge is how to recognize babies at intrapartum risk both before and during labour. A detailed description of prepartum and intrapartum risk factors is available. A close surveillance of labour and intrapartum time should be mandatory as the valuation of all available data from obstetrical examination, cardiotocography, ultrasound and labour progression to reach the correct diagnosis with the lowest possible rate of error. The close monitoring should not exclude a humanized and compliant attitude versus labouring women and their families. We analysed the Cagliari Neonatal Intensive Care Unit (NICU) activity during the last four years considering 22 asphyxiated babies (coming from 9 different hospitals) who underwent hypothermia treatment. The main result was that the need to resuscitation procedures at birth correlates with adverse outcomes. Asphyxia still remains a matter of great concern also as medico legal claims. Considering that neonatal encephalopathy is a heterogeneous condition, it is unlikely that it will be eradicated. However, a comprehensive evaluation of all risk factors and of intrapartum surveillance available tools may reduce as much as possible adverse events. Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou